Exploring the interplay between macroeconomic demand and supply factors and the unsold housing market : a descriptive study / Anis Anisah Hashim and Asmma’ Che Kasim - Hashim, Anis Anisah; Che Kasim, Asmma’ (2023)
The factors influencing the issue of unsold residential units in Kinta, Perak, from the perspective of the public. The problem of unsold properties in Malaysia is a recurring concern, with many people unaware of the underlying reasons behind it. NAPIC reports indicate a 3.3% increase in unsold residential units from 2019 to 2020, and Perak alone has over 2,900 unsold units. The research aims to identify and rank these factors affecting unsold residential units in Kinta, Perak, with two main objectives: first, to identify the factors influencing the issue, and second, to rank these factors based on public perception. The study adopts a quantitative approach, utilizing a questionnaire with 24 questions in sections A, B, and C. The data was gathered through an online survey, with 119 respondents, which is considered an acceptable sample size. Descriptive analysis, including mean and RII calculations, was employed to rank the factors. The analysis revealed that the lack of nearby public amenities was the top factor agreed upon by the respondents, followed by the current housing prices contributing to the increase in unsold residential units. Overall, this research emphasizes the importance of finding solutions and urges policymakers to develop a new framework to address the issue of unsold residential properties in Kinta, Perak. By understanding the factors influencing this phenomenon from the public perspective, appropriate measures can be taken to address the root causes and foster a more balanced and sustainable property market in the region